2006
DOI: 10.1017/s002221510600079x
|View full text |Cite
|
Sign up to set email alerts
|

Does the slow compression technique of hyperbaric oxygen therapy decrease the incidence of middle-ear barotrauma?

Abstract: The slow compression method of HBOT proved to be both safe and superior to the standard compression technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…Vahidova et al 3 reported 30.9% of smoking in their sample, but did not correlate this with MEB. Uzun 14 , in a study of MEB in divers, found no association between smoking and MEB.…”
Section: Clinical Historymentioning
confidence: 69%
See 2 more Smart Citations
“…Vahidova et al 3 reported 30.9% of smoking in their sample, but did not correlate this with MEB. Uzun 14 , in a study of MEB in divers, found no association between smoking and MEB.…”
Section: Clinical Historymentioning
confidence: 69%
“…HBOT is not without risks and the middle ear barotrauma (MEB) is its most common side effect 3,4 . MEB consists in the appearance of lesions on the tympanic membrane (TM) and/or tympanic cavity, secondary to pressure variation unable to be compensated by the Eustachian tube (ET).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active maneuvers (e.g., Valsalva) to open the Eustachian tubes are usually required to equalize middle ear pressure. Thus, not surprisingly a slower compression will allow time for patients to perform the active maneuvers and reduce the rate of MEB as demonstrated by Vahidova, et al [3]. As the pressure gradient increases, these active maneuvers become increasingly difficult to perform [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, three concurrent practices are used to reduce the incidence of MEB: i) assessment to identify patient at risk of MEB; ii) teaching patients correct ear equalization techniques; iii) slow chamber compression. Vahidova et al demonstrated that the use of a slow compression technique (1.1 meters/minute vs. 2.8 meters/ minute) significantly reduced the incidence of middle ear barotrauma from 52.3% to 28.5% [3]. Most centers compress their patients to 242 kilopascals/kPa, or 2.4 atmospheres absolute/ATA over 10 to 14 minutes depending on patients' comfort and on their ability to equalize their ears.…”
Section: Introductionmentioning
confidence: 99%